Adaptive Reuse - James Dubois (Oz, 1989)
Fifth Year Interior Architecture Studio: text by James Dubois; students whose work is featured are Patrick Duegaw, Lara Frashier, Amy Knezevich, Kent Williams, and Tom Willow.